DEVELOPMENT OF INTERACTIVE MULTIMEDIA FOR JUMPUT BATIK MATERIALS LEARNING CULTURAL ARTS AND CRAFTS - Lestari, Puput Puji; Nurharini, Atip (Universitas Negeri Semarang, 2020)
The objective of this study was to develop a design and investigate the feasibility of interactive multimedia for batik jumput lesson. The method employed in this study was Research and Development (R&D). The research subject was the five graders of SDN Wonolopo 03. The techniques of data analysis employed preliminary data analysis, t-test, and gain test. The result of the study showed that (1) The design of developing interactive multimedia for batik jumput lesson was developed based on the teachers 'and students' needs which indicated that the teachers and students required an interactive multimedia for batik jumput lesson, (2) The result of materials validity obtained 62.85% in the feasible criteria, the result from media experts obtained 80% in the feasible criteria, the result of practitioner validity obtained 95. 5% in the very feasible criteria. (3) The learning outcomes increased by 0.407 for knowledge aspect, and 0.380 for skill aspect, each of which was in the medium criteria. In conclusion, the interactive multimedia with adobe flash for batik jumput materials is feasible and effective to be used in batik jumput lesson for grade 5 SDN Wonolopo 03.